MEDIA KOMIK PADA MATERI CERITA DONGENG UNTUK KETERAMPILAN MEMBACA SISWA KELAS III - Heny Kusuma Widyaningrum; Cerianing Putri Pratiwi (JURNAL DIMENSI PENDIDIKAN DAN PEMBELAJARAN, 2019)
The process of communication in literature appreciation learning willbe more effective if supported by the media. One of the development media for students is comics. The objection of this study is to develop and produce a fairy tale comic and to know the results of comic product so it proper to be used as a medium of literature appreciationlearning. This type of research is Research and Development (R D), adapt from the Warsito's development model. Determination of proper level of comic media is based on validation test of experts and student test through questionnaire and questioning test.The result of the teaching materials done by material experts showed the properity of 85% and the media expert of 87,5%. Both experts indicate that the media is valid and ready to be implemented. The results of the test to the students show the properity of 92,50% and stated as valid. Student learning outcomes  after showing the use of teaching materials has a value of 85,22 and can support the properity of teaching materials after tested to students without the need to be revised.Keywords: comic media ,fairy tale, and  reading skills. The process of communication in literature appreciation learning willbe more effective if supported by the media. One of the development media for students is comics. The objection of this study is to develop and produce a fairy tale comic and to know the results of comic product so it proper to be used as a medium of literature appreciationlearning. This type of research is Research and Development (R D), adapt from the Warsito's development model. Determination of proper level of comic media is based on validation test of experts and student test through questionnaire and questioning test.The result of the teaching materials done by material experts showed the properity of 85% and the media expert of 87,5%. Both experts indicate that the media is valid and ready to be implemented. The results of the test to the students show the properity of 92,50% and stated as valid. Student learning outcomes  after showing the use of teaching materials has a value of 85,22 and can support the properity of teaching materials after tested to students without the need to be revised.